2016
DOI: 10.1177/0194599816661703
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Determinants of Otitis Media in an Indigenous Filipino Population

Abstract: Objective To identify genetic and environmental risk factors for otitis media in an indigenous Filipino population Study Design Cross-sectional study Setting Indigenous Filipino community Subjects and Methods Clinical history and information on breastfeeding, tobacco smoke exposure and swimming were obtained from community members. Heads of households were interviewed for family history and personal beliefs on ear health. Height and weight were measured. Otoscopic findings were described for presence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…In mixed models analysis, in which family branch or household was analyzed as a random effect, otitis media was associated with both gingivitis ( p = 0.0007) and A2ML1 variants ( p = 0.048). Neither age nor sex was associated with otitis media, consistent with previous findings (Santos‐Cortez, Reyes‐Quintos et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mixed models analysis, in which family branch or household was analyzed as a random effect, otitis media was associated with both gingivitis ( p = 0.0007) and A2ML1 variants ( p = 0.048). Neither age nor sex was associated with otitis media, consistent with previous findings (Santos‐Cortez, Reyes‐Quintos et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous discovery of A2ML1 (MIM 610627), which encodes alpha‐2‐macroglobulin‐like‐1, as an autosomal dominant gene for otitis media susceptibility suggested that rare variants play a role in otitis media pathology (Santos‐Cortez et al, ). An indigenous Filipino population with an approximately 50% prevalence of otitis media was found to have an A2ML1 duplication variant as the strongest predictor for disease (Santos‐Cortez, Reyes‐Quintos et al, ). The same duplication variant was also identified to be associated with otitis‐prone status in US children (Santos‐Cortez et al, ).…”
Section: Introductionmentioning
confidence: 84%
“…Findings have shown that the A2ML1 genotype is the strongest predictor of otitis media occurrence within this population (Santos‐Cortez et al. ).…”
Section: Research Priorities In Medical Genetics and Genomicsmentioning
confidence: 86%
“…In another related study on otitis media and the indigenous Filipino population, risk factors such as environmental variables, A2ML1 variant carrier status, and middle ear bacteria were analyzed. Findings have shown that the A2ML1 genotype is the strongest predictor of otitis media occurrence within this population (Santos-Cortez et al 2016).…”
Section: Research Priorities In Medical Genetics and Genomicsmentioning
confidence: 87%
“…I n t h e P h i l i p p i n e s , a d u p l i c a t i o n v a r i a n t c.2478_2485dupGGCTAAAT (p.Ser829Trpfs*9) within the A2ML1 gene was found to be associated with OM in an indigenous Negrito community (Santos-Cortez et al 2015); this variant confers an increased risk for all types of OM (Santos-Cortez et al 2016b). In this indigenous Filipino population of around 200 individuals from 30 household units, the prevalence of OM was~50% (Santos-Cortez et al 2016b). Historically, this indigenous community has inhabited this region for centuries but they were racially segregated due to their physical features (e.g., dark-colored skin, short stature, flat nose, curly hair).…”
Section: Introductionmentioning
confidence: 96%